Gen-Z Saving Behavior: The Role Financial Literacy in Digital Payment Mediated: Gen-Z Saving Behavior: The Role Financial Literacy in Digital Payment Mediated - Hidayat, Andi; Nurhadi N, Muhammad Nurhadi; Nurhidayah, Nurhidayah (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to analyze the direct and indirect influence of financial literacy on the saving behavior of Generation-Z with digital payment as a mediating variable, where this study uses a quantitative approach, where the object of this research is Generation-Z in Makassar City, the sample used in this study is 150 people with the criteria of Generation-Z who use the application and have savings, data analysis used in this study using partial least squares path modeling (PLS-SEM). The results of the study showed that the direct influence of financial literacy on saving behavior did not have a significant effect, the direct influence of financial literacy on digital payments had a significant effect, digital payments had a significant effect on saving behavior, and digital payments had a significant effect in mediating the relationship between financial literacy and saving behavior.